The effect of follicular phase length on cycle outcomes and endometrial development in gonadotrophin ovarian stimulation/intrauterine insemination cycles. Issue 3 (March 2020) - Bakkensen, Jennifer B.; Christou, Georgios; Dimitriadis, Irene; James, Kaitlyn; Souter, Irene
Abstract: Research question: Does a shorter follicular phase length (FPL) affect cycle outcomes and endometrial development among women undergoing gonadotrophin ovarian stimulation/intrauterine insemination (OS/IUI)? Design: Retrospective cohort study of 4773 OS/IUI cycles among 2054 patients. FPL was analysed first continuously, then dichotomously using an arbitrary cut-off at the 15th percentile (8 days) to divide cycles into shorter and longer FPL groups. Receiver operating characteristic (ROC) curves were constructed to further analyse the impact of FPL on all outcomes. Primary outcomes included clinical pregnancy, spontaneous abortion, multiple pregnancy and non-viable (ectopic/biochemical) pregnancy rates (CPR, SABR, MPR and NVPR, respectively). Secondary outcomes included endometrial thickness. All analyses controlled for age, day 3 FSH and body mass index. Results: When analysing FPL continuously, CPR increased by 6.0% (adjusted odds ratio [aOR] 1.06, 95% CI 1.03–1.09, P <  0.001) with each additional follicular phase day. Similarly, in the dichotomous analysis, cycles with a longer FPL resulted in higher CPR with 45% higher odds of clinical pregnancy (aOR 1.45, 95% CI 1.07–1.97, P  = 0.018). No effect of FPL was noted on NVPR, SABR or MPR. Endometrial thickness increased by 0.09 mm (95% CI 0.06–0.12, P <  0.001) with each additional FPL day and was increased in the longer compared with the shorter FPL group (adjusted mean difference 1.08 mm, 95% CI 0.81–1.34, P <  0.001). Conclusions: The data suggest that in gonadotrophin OS/IUI cycles, FPL might impact both chance of clinical pregnancy and endometrial thickness, independent of maternal age and ovarian reserve.